Rethinking global political economy : emerging issues, unfolding odysseys - Tétreault, Mary Ann, 1942- (London ; New York : Routledge, 2003)
Innovative approaches to the fundamental issues of the global political economy, in particular post Cold War development, analyses of capital and negative aspects of globalization.
pt. 1. Introduction -- pt. 2. Aids to navigation -- pt. 3. Sacking the city -- pt. 4. Repair of the world -- pt. 5. Conclusion.
Includes bibliographical references (pages 238-283) and index.
Print version record.
eBooks on EBSCOhost
Keywords: International economic relations; Globalization -- Economic aspects; Globalization -- Social aspects; Globalization -- Political aspects; Mondialisation; Mondialisation -- Aspect social; Mondialisation -- Aspect politique; globalism; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Economics; Globalization -- Economic aspects; Globalization -- Political aspects; Globalization -- Social aspects; International economic relations